KOLABORASI DALAM PENANGANAN PERMUKIMAN KUMUH MELALUI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN SUKARAMAI KECAMATAN PEKANBARU KOTA TAHUN 2016-2017 - Bella Makruffi Fitriana; M.Y.Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Slums are uninhabitable settlements due to building irregularities, high levels of building density, and the quality of buildings and infrastructure that do not meet the requirements. The government makes the settlement area a national program to realize habitable settlements through the KOTAKU program. To carry out the program, it requires collaboration between the parties involved in order to realize the objectives of the KOTAKU program. Collaboration is carried out by fulfilling the principle of collaboration, namely participation, communication, trust, sharing, and acceptable. The formulation of the problem in this study is (1) How is the collaboration in handling slums in Sukaramai Village Pekanbaru Kota District? (2) What are the obstacles experienced in handling slum settlements in Sukaramai Village Pekanbaru Kota District? The objectives of this research are (1) To describe collaboration in handling slums in Sukaramai Village Pekanbaru Kota Subdistrict. (2) To describe the obstacles experienced in handling slums in Sukaramai Village Pekanbaru Kota District. The results of this study are that there are still many parties involved in collaboration not adhering to the principle of collaboration so that collaboration does not work effectively. And in the implementation of the program, not all parties were involved from the beginning to the end of the program implementation. Besides that, there are also external and internal inhibiting factors in managing slums, so that the objectives of the program cannot be fully achieved. External factors include budget constraints and internal factors are lack of public awareness about clean and healthy living behavior. Keywords: Collaboration, Slum area, KOTAKU Program